Suffering : Gospel hope when life doesn't make sense - Tripp, Paul David, 1950- (Crossway, 2018)
"Author Paul David Tripp "weaves together his personal story, years of counseling experience, and biblical insights to help those in the midst of suffering, identifying six traps to avoid and six comforts to embrace."--ipage.ingramcontent.com.